Association between sarcopenia and the severity of diabetic polyneuropathy assessed by nerve conduction studies in Japanese patients with type 2 diabetes mellitus. Issue 8 (21st March 2022) - Mikura, Kentaro; Kodama, Eriko; Iida, Tatsuya; Imai, Hideyuki; Hashizume, Mai; Kigawa, Yasuyoshi; Tadokoro, Rie; Sugisawa, Chiho; Endo, Kei; Iizaka, Toru; Otsuka, Fumiko; Nagasaka, Shoichiro
Abstract: Aims/Introduction: This study examined the association between the severity of diabetic polyneuropathy (DPN) based on the Baba classification, and sarcopenia and its related factors. Materials and Methods: The participants were 261 patients with type 2 diabetes mellitus. DPN was classified as stages 0–4 according to the Baba classification. Sarcopenia was diagnosed based on measurements of the skeletal mass index, grip strength and walking speed, using the Asia Working Group for Sarcopenia 2019 diagnostic criteria. Results: The median age of the participants was 67 years, the proportion of men was 58.6%, the median estimated duration of diabetes was 10 years and the median values for glycated hemoglobin were 10.3%. With regard to DPN, the prevalence of Baba classification stages 0–2 was 90.8% ( n  = 237), and that of stage 3 or 4 was 9.2% ( n  = 24). The prevalence of sarcopenia was 19.9%. A trend toward an increase in the frequency of slow walking speed was seen as the stage of DPN progressed. The frequencies of sarcopenia and slow walking speed were higher in the group with the Baba classification stages 3 and 4 than in the group with stages 0–2. On multiple logistic regression analyses, however, DPN was not significantly related to sarcopenia and walking speed. Conclusions: Although severe DPN might be related to sarcopenia, the frequency of severe DPN is low in the clinical setting, indicating that its contribution to sarcopenia is modest. Abstract : We evaluated the association between the severity of diabetic polyneuropathy and sarcopenia in type 2 diabetes patients. The results showed that the severity of diabetic polyneuropathy was not associated with sarcopenia, and factors such as age, were significantly associated with it.